Chemical chaperone 4-phenylbutylate reduces mutant protein accumulation in the endoplasmic reticulum of arginine vasopressin neurons in a mouse model for familial neurohypophysial diabetes insipidus. (24th August 2018) - Tochiya, Masayoshi; Hagiwara, Daisuke; Azuma, Yoshinori; Miyata, Takashi; Morishita, Yoshiaki; Suga, Hidetaka; Onoue, Takeshi; Tsunekawa, Taku; Takagi, Hiroshi; Ito, Yoshihiro; Iwama, Shintaro; Goto, Motomitsu; et al.
Highlights: We examined therapeutic effects of the chemical chaperone 4-PBA in FNDI mice. 4-PBA ameliorated accumulation of mutant AVP precursors in the ER of AVP neurons. 4-PBA attenuated polyuria and AVP neuron loss in FNDI mice. Abstract: Familial neurohypophysial diabetes insipidus (FNDI), characterized by progressive polyuria and loss of arginine vasopressin (AVP) neurons, is an autosomal dominant disorder caused by AVP gene mutations. Our previous studies with FNDI model mice demonstrated that mutant proteins accumulated in the endoplasmic reticulum (ER) of AVP neurons. Here, we examined therapeutic effects of the chemical chaperone 4-phenylbutylate (4-PBA) in FNDI mice. Treatment with 4-PBA reduced mutant protein accumulation in the ER of FNDI mice and increased AVP release, leading to reduced urine volumes. Furthermore, AVP neuron loss under salt loading was attenuated by 4-PBA treatment. These data suggest that 4-PBA ameliorated mutant protein accumulation in the ER of AVP neurons and thereby prevented FNDI phenotype progression.